Sociodemographic, clinical, laboratory, treatment and prognostic characteristics of 156 generalized pustular psoriasis patients in Turkey: a multicentre case series. (13th April 2022) - Kara Polat, A.; Alpsoy, E.; Kalkan, G.; Aytekin, S.; Uçmak, D.; Yasak Güner, R.; Topkarcı, Z.; Yılmaz, O.; Emre, S.; Borlu, M.; Türkoğlu, Z.; Özkök Akbulut, T.; et al.
Abstract: Background: Generalized pustular psoriasis (GPP) is a rare and severe inflammatory disease characterized by widespread and superficial sterile pustules on an erythematous background. Objectives: This multicentre study aimed to determine the clinical profile and course in a large cohort of patients with GPP. Methods: One hundred and fifty‐six GPP patients (mean age, 44.2 ± 18.7 years) who met the diagnostic criteria of the European Consensus Report of GPP were included in the study. Sociodemographic characteristics, quality of life, triggering factors of the disease, clinical, laboratory, treatment and prognostic features were evaluated. Results: 61.5% of the patients were female. The rate of working at or below the minimum wage (≤$332.5/month) was 44.9%. Drugs (36.5%) were the most common trigger. While hypocalcaemia (35.7%) was the most important cause of GPP during pregnancy, systemic steroid withdrawal (20%) was the most frequently reported trigger for infantile/juvenile and mixed‐type GPP (15%) ( P  < 0.05). Acute GPP (53.8%) was the most common clinic. Nails were affected in 43.6% of patients, and subungual yellow spots (28.2%) were the most common change. In annular GPP, fever ( P  < 0.001) and relapse frequency ( P  = 0.006) were lower than other subtypes, and the number of hospitalizations ( P  = 0.002) was lower than acute GPP. GPP appeared at a later age in those with a history of psoriasis ( P  = 0.045). DLQI score ( P  = 0.049) and joint involvement ( P  = 0.016) were also higher in this group. Infantile/juvenile GPP was observed in 16.02% of all patients, and arthritis was lower in this group (24.4 vs. 16%). GPP of pregnancy had the worst prognosis due to abortion observed in three patients. Conclusions: Recent advances in treatment have improved mortality associated with GPP, but abortion remains a significant complication. Although TNF‐α inhibitors have proven efficacy in GPP, they can also trigger the disease. Mixed‐type GPP is more similar to acute GPP than annular GPP with systemic manifestations and course.